Food Filtering Process of Daphnia Carinata King to Assess the Water Soluble Detergent - Soelaksono Sastodihardjo; Hilda Zulkifli (Institute for Research and Community Services (LPPM) ITB, 1987)
Abstract. Water organisms such as zooplankton and fish were used quite often as indicators for water quality in connection with chemically toxic substance in water. Several criteria could be use such as LC50, population index, and physiological phenomena. Bioassay that rely on this physiological phenomena was meant to measure the sublethal effect of the suspected toxic substance on the organisms. Further development of sublethal bioassay using filtering rate of Daphnia carinata (Cooley, 1977; McMahon, 1966) has taken place for a certain detergent. Yeasts cells tagged with 32P were used as food for Daphnia carinata and the filtering rate was measured from the radioactivity of these crustaceans after a certain period of feeding time. Comparison was made between the feeding rate in the medium with and without the detergent and they appeared to be different. Sari. Organisme air seperti zooplankton dan ikan telah sering digunakan untuk menafsirkan kehadiran senyawa kimia yang terlarut dalam air sehubungan dengan masalah kualitas air. Kriteria untuk menyatakan kehadiran tersebut dapat dinyatakan dalam bentuk LC50, indeks populasi, dan gejala fisiologis. Uji hayati yang menggantungkan pada gejala fisiologis ini mempunyai sasaran untuk mengukur dampak subletal suatu senyawa terhadap organisme. Perkembangan lebih lanjut adalah penggunaan laju penyaringan dari Daphnia carinata (Cooley, 1977; McMahon 1966) untuk menafsirkan kehadiran sejenis detergen. Dalam hal ini laju penyaringan diukur dengan menghitung jumlah rugi yang bertanda 32p yang termakan oleh udang tersebut. Dilakukan pembandingan antara laju penyaringan Daphnia yang berada pada medium tanpa dan dengan detergen.